(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2023)
The Lagos-Shagamu-Abeokuta Expressway is a globally important biodiversity hotspot and is facing rapid loss in floristic diversity and changing patterns of vegetation due to various biotic and abiotic factors. This has necessitated the qualitative and quantitative assessment of floral diversity and population structure. The vegetation survey along this route was conducted using the systematic sampling methods. Three sample plots of 50 m x 50 m were laid in alternate side at 100m interval. In each sample plot, all living trees (with GBH at 1.3 m of trees) greater than or equal to 3 m high at midpoint were measured. A total of 4212 individuals representing 134 species, 117 genera, and 48 families were recorded. Fabaceae was the dominant family in this route with 22 species, followed by Euphorbiaceae (8 species), Apocynaceae (8 species), and Poaceae (5 species). Among genera, Senna was followed by Ficus, Terminalia, Cola, Clerodendrum, Albizia, and Alchornea. The population structure of woody species based on diameter class distribution reflected reversed J-shape. The species diversity indexes for dominance (0.02, 0.06), Simpson index value (0.97, 0.93), Shannon–Weiner (3.91, 3.25), evenness (0.59, 0.52) and Margalef (11.22, 6.15) were recorded for arboreal and non-arboreal species respectively. Results obtained revealed high diversity of woody species in the vegetation along this route. The non-arboreal species along this route is threatened by continuous animal grazing, intensification of commercialized farming and invasive species. The information on tree species structure and function can provide baseline information for the conservation of the biodiversity of the tropical forest in this area.